O sistema de referenciação multimodal de crianças com síndrome de down em engajamento conjunto - Nóbrega, Paulo Vinícius Ávila (2017)
A large variety of studies are found in the field of referenciation. According Textual Linguistics, reference is not a reflection of the reality of the things in the world, but a negociation of meanings between subjetcs in the real or virtual interaction (MARCUSCHI, 2002; 2005; MONDADA; DUBOIS, 2003). For a long time it was known that the only way of bulding meanings was through verbal language, oral or written. Although that point of view had been deeply taken into consideration by Linguistic, another opinion gets notoriously attention when the language is seen as a combination of distincts language ways in the same field. The multimodality suggests that the variation of the language are not complementing one another or happen alone. Vocal, gestual and visual production happen at the same time (MCNEILL, 1999; KENDON, 1982). Therefore, our objective is analyzing how the multimodal referenciation works in joint engagement scenes among three Down Syndrome (DS) children. Our data were collected at the Speech Therapy Clinic, at UFPB, and are composed of 17 meetings between children and speech therapists. Children were 2, 6 and 8 years old at the beginning of data collection. The appointment were filmed and each one lasts around 30 minutes. We defend the idea that the three children who were involved in the scenes (TOMASELLO, 2003; 2005; 2009) with the speech therapists and who were using distincts language ways make emerge Multimodal Referenciation Systems (MRS) as a resulto f negociation about the discourse objects (DO), along the meetings. These DO are negociated throught referenciation relations known as repetition, association, reiteration and connection. The direction of the most promising gaze in the meetings was the sharing of expectation, followed by the accompanying gaze. Deictic gestures were always highlighted, followed by iconic gestures. As for the semiotic character, these gestures were less abstract, less metaphorical, and had their own configuration. This kind of work may helps the engagement of educational and clinical professional when they begin to notice the language throught multimodal referenciation.